Pengaruh Bauran Pemasaran dan Dampak Pandemi Covid-19 Terhadap Keputusan Pembelian Makanan Siap Saji - Mochamad Reza Adiyanto; Nirma Kurriwati; Triana Setiyarini (JURNAL ADMINISTRASI KANTOR, 2022)
The purpose of this study was to determine the demographic characteristics of fast food consumers and to analyze the effect of marketing mix variables (product, price, place and promotion) and environmental factors caused by the Covid-19 pandemic on consumer buying decisions for fast food. The type of data used is quantitative primary data. Primary data were obtained from distributing questionnaires to consumers who bought ready-to-eat food at Sabana Fried Chicken Restaurant, Bluru Permai Sidoarjo Branch. The sample is determined on purpose (convenience sampling). Respondents amounted to 100 people. The results showed that the demographic characteristics of fast food consumers were the majority aged 17-24 years, female, had 3-4 members in one family and had an expenditure of Rp. 1 million – Rp. 2 million in one month. Based on multiple regression analysis shows that the product factor (X1) and environmental factors (X5) have a significant effect on the decision to buy fast food (Y). While the factors of Price (X2), Place (X3) and Promotion (X4) have no significant effect. This study implies that culinary entrepreneurs need to focus on marketing to consumers who have an age range of 17 - 24 years and are female because they have a large enough market opportunity. One of the strategies carried out is by expanding product lines and collaborating with online food delivery services such as Go Food and Grab Food as a solution to the negative impacts caused by the Covid-19 pandemic.